PENGARUH STATUS KEANGGOTAAN KOPERASI ISM MITRA KARYA BAHARI TERHADAP PENDAPATAN RUMAH TANGGA NELAYAN DI PULAU PASARAN BANDAR LAMPUNG - Putri S, Ayu Permata; Lestari, Dyah Aring Hepiana; Rangga, Kordiyana K (Lampung University, 2016)
This research aims to determine: the amount and effect of membership status on the income of fisherman, the amount of economic benefits, and the amount and effect of membership status on the income of fisherman’s household. This research was conducted in Pasaran Island which most people are fishermen. The number of cooperative member respondents was 35 people, while the number of non-cooperative member respondents was 30 people. This research was conducted by survey method and the data was analyzed by income analysis and simple linear regression analysis. The result showed that the income of catch fish business had different amount in different seasons. The income of fisherman's cooperative members was higher than non-fisherman's cooperative members because of the significant effect on membership status to fisherman's household income. The average household income of fisherman members from economic benefits cash value was Rp90,000.00 per year and the average household income of fisherman members from economic benefit calculated value was Rp1,035,637.14 per year. The total household income of cooperative members was Rp31,752,000.00 per year, this was higher than non-cooperative members which was Rp23,226,426.67 per year. Therefore, membership status had significant effect on fisherman's household income. Key words: economic benefit of cooperative, income, membership status